Effects of a caspase and a calpain inhibitor on resting energy expenditures in normal and hypermetabolic rats: a pilot study - Vana, P G; LaPorte, H M; Kennedy, R H; Gamelli, R L; Majetschak, M (Physiological research, 2016)
Several diseases induce hypermetabolism, which is characterized by increases in resting energy expenditures (REE) and whole body protein loss. Exaggerated protein degradation is thought to be the driving force underlying this response. The effects of caspase and calpain inhibitors on REE in physiological and hypermetabolic conditions, however, are unknown. Thus, we studied whether MDL28170 (calpain inhibitor) or z-VAD-fmk (caspase inhibitor) affect REE under physiological conditions and during hypermetabolism post-burn. Rats were treated five times weekly and observed for 6 weeks. Treatment was started 2 h (early) or 48 h (late) after burn. In normal rats, MDL28170 transiently increased REE to 130 % of normal during week 2-4. z-VAD-fmk reduced REE by 20-25 % throughout the observation period. Within 14 days after burns, REE increased to 130+/-5 %. Whereas MDL28170/early treatment did not affect REE, MDL28170/late transiently increased REE to 180+/-10 % of normal by week 4 post-burn. In contrast, with z-VAD-fmk/early REE remained between 90-110 % of normal post-burn. z-VAD-fmk/late did not affect burn-induced increases in REE. These data suggest that caspase cascades contribute to the development of hypermetabolism and that burn-induced hypermetabolism can be pharmacologically modulated. Our data point towards caspase cascades as possible therapeutic targets to attenuate hypermetabolism after burns, and possibly in other catabolic disease processes.
Keywords: Animals; Amino Acid Chloromethyl Ketones; chloromethylketony aminokyselin; energetický metabolismus; dipeptidy; Dipeptides; Pilot Projects; Energy Metabolism; pilotní projekty; Drug Evaluation, Preclinical; Rats, Sprague-Dawley; metabolické nemoci; Cysteine Proteinase Inhibitors; preklinické hodnocení léčiv; Male; potkani Sprague-Dawley; Burns; inhibitory kaspas; Metabolic Diseases; zvířata; mužské pohlaví; inhibitory cysteinových proteinas; popálení; Caspase Inhibitors